Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7591685 ZenodoArchiveConcept: 7591684 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7591685 10.53832/edtechhub.0146 2405685:J8IB7LVG 2405685:V4EVQ39I
Keywords: _r:AddedByZotZen

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2339240:SCCGE8HG 2405685:HEXCEXFK 2405685:NBAIXDE4 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

Elevating Education at High Altitude: EdTech implementation in Gilgit-Baltistan - Aslam, M. Nawaz; Mazari, Haani; Hayat, Amal; Hassan, Syed Mustafa; Afzal, Nimra; Zahir, Jazib; Ministry of Federal Education and Professional Training, Pakistan (EdTech Hub, 2024)
Gilgit-Baltistan, located in the northernmost part of Pakistan, is a region known for its mountainous geography. Its complex geography creates challenges for education, such as geographic isolation and infrastructural limitations. While technology offers the potential to overcome these barriers of isolation, several infrastructural and capacity barriers prevent equitable access to EdTech. The Government of Gilgit-Baltistan has strived to respond to these barriers by introducing a more holistic EdTech implementation model that aims to contextualise solutions toward infrastructural and capacity needs. The study investigates the government’s reforms and initiatives to identify good practices and provide further recommendations to enhance EdTech implementation in Gilgit-Baltistan. It also considers the strengths and opportunities that shape Gilgit-Baltistan’s approaches to implementing EdTech through the 'STEAM' and 'Smart Schools' interventions. Key elements of the government’s approach to implementing EdTech include a focus on aligning intervention design with infrastructural needs, for example, by considering solarisation to improve access to power sources. The introduction of ‘hot spots’ to enable offline access to an LMS has enabled schools to access preloaded, curriculum-aligned teaching and learning materials. To overcome challenges in teacher capacity, the government invested in ‘Tech Fellows’ (IT graduates who support teachers with classroom integration) to bridge the gap between limited digital skills and implementation requirements. In this study, we find areas through which this model can be strengthened and highlight examples that implementers in low-resource settings can learn from. low-resource contexts; blended learning; Pakistan; Gilgit-Baltistan; digital skills; teacher training; solar energy; offline solutions An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11652091 ZenodoArchiveConcept: 11652090 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1032 2405685:VHFR6UIT
Keywords: _r:AddedByMyEducationEvidence

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
This report examines gender disparities in the use of educational technology (EdTech) among students in Pakistan, with the aim of informing policies that foster more inclusive and equitable digital learning environments. Drawing on data from a survey of over 2,000 teachers and interviews with EdTech stakeholders in Islamabad, the report explores how sociocultural norms and parental attitudes shape differential access to and use of EdTech at home—particularly disadvantaging female students. It identifies key barriers including limited access to affordable internet and devices, low digital literacy among parents (especially mothers), and prevailing gender norms that restrict girls’ engagement with technology. The findings highlight an urgent need for targeted interventions that address both infrastructural and sociocultural challenges. Recommendations include: expanding subsidised internet and device access in underserved areas; launching community-based digital literacy programmes for parents; creating safe online spaces for female students; promoting positive gender representation in media; and organising inclusive EdTech initiatives to increase girls’ participation. By tackling these barriers through coordinated action, the report offers a roadmap to bridge the gender gap in EdTech adoption and enhance educational equity in Pakistan. Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14973585 ZenodoArchiveConcept: 14973584 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1057 10.53832/edtechhub.1099
Keywords: _r:AddedByMyEducationEvidence

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651935 previousDOI: 10.5281/zenodo.4923094 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4923094 10.5281/zenodo.5651935 2339240:6ELB8P84 2339240:HZ3EBZ29 2405685:79JJ5T29 2405685:P8IAN448 2405685:RU8ET9S2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524805 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524805 10.53832/edtechhub.0048 2339240:5D6SMESW 2339240:7NDUJC6J 2339240:M8IZH5DT 2339240:SIZUDNKL 2339240:XAXIKZJX 2339240:YPDDA6JD 2405685:45G9SKWR 2405685:5ENZ6TFU 2405685:EJ4PXU4S 2405685:JZM7W6QE 2405685:LCHJ5D5W 2405685:RUAJ8C8M
Keywords: _r:AddedByZotZen

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7568301 ZenodoArchiveConcept: 7568300 KerkoCite.ItemAlsoKnownAs: 2129771:VEW2PXA5 10.5281/zenodo.7568301 10.53832/edtechhub.0177 2405685:2AN8XVIA
Keywords: _r:AddedByZotZen